Outcome and Mortality of Stroke - J Gordon Millichap (Pediatric Neurology Briefs, 2002)
Death certificate data for ischemic and hemorrhagic stroke (subarachnoid hemorrhage [SAH] and intracerebral’ hemorrhage [ICH] in children under 20 years of age in the United States were analyzed for a 20 year period at the University of California, San Francisco.